A balanced approach to falls prevention: Application in the real world. (24th March 2018) - Jancey, Jonine; Wold, Catrina; Meade, Rachel; Sweeney, Roisin; Davison, Erica; Leavy, Justine
Abstract: Background: Falls place a heavy burden on the health system, impacting on an individual's quality of life, often resulting in a fear of falling, reduction in independence and at times admission to residential care. This study aimed to determine health professionals' confidence in discussing falls prevention strategies, topics discussed and the barriers and enablers to falls prevention discussions with clients aged 60 years and over. Method: A cross‐sectional self‐complete online survey was undertaken with a sample of health professionals (n = 191) who had engaged in the services of the Stay On Your Feet ® programs delivered by the Injury Matters in Western Australia (WA). Results: The majority of participants were physiotherapists (25.7%), registered nurses (17.8%) and occupational therapists (11%) located in metropolitan (56%) and regional (44%) WA. Most health professionals (80.2%) were "highly" confident discussing falls prevention strategies. Discussion of falls prevention included the benefits of strength and balance exercises (83%), eating a healthy diet (78.7%), regular eyesight checks (64.5%), reviewing medications (54.8%) and exposure to sunlight (50.3%). The main enablers to falls prevention were knowledge (89.7%), skills to identify (77.7%) and implement (66.3%) falls prevention strategies, and access to printed resources (74.9%), while the main barrier was appointment times (14.6%). Conclusion: Health professionals' indicated that they are confident in discussing falls prevention strategies, and although a range of falls prevention strategies were discussed, limited attention was directed at the pharmacists' review of medications, eyesight checks and increasing vitamin D levels. So what?: Health professionals are discussing falls prevention strategies with their clients. A more multifaceted approach should be encouraged with an emphasis on all prevention strategies.